(untitled) (Psicologia USP, 1997)
Stimuli present in the “causal texture” of the organismenvironment relation are not simply specified by physical characteristics externally defined, but as part of a processing. The several ways of stimuli processing which control the behavior of organisms evolve external stimuli and also internal representations of these stimuli and their relations. The notion of representation is related to the processing of information coded by the organism and the analysis of their own transformations. Pavlovian conditioning studies show that animals are able to operate complex representations of inter-event relations. The associative and combinatory properties of neural representation produce a mechanism of activation of hierarchical celular assembly, generating diversity by a neuroseletion processing. The complex organization of representations in animals paralels human imagery event functions and its study contributes to the notion of evolutionary continuity of perception and memory mechanisms between animals and humans.